McArdle Disease vs. Stiff-Person Syndrome: A Case Report Highlighting the Similarities Between Two Rare and Distinct Disorders - Godbe, Kerilyn; Malaty, Giovanni; Wenzel, Alyssa; Nazeer, Sahana; Grider, Douglas J.; Kinsey, Adrienne (Frontiers in Neurology, 2020)
McArdle disease is a rare autosomal recessive disorder of muscle glycogen metabolism that presents with pain and fatigue following exercise. Comparatively, Stiff-Person Syndrome is thought to be an autoimmune-related neurologic process typically characterized by fluctuating muscle rigidity and spasm, the onset of which can be insidious, and acutely exacerbated by sensory stimuli. In this case report, we discuss a 41-year-old male who presented to the emergency department due to sudden-onset weakness and chest pain while moving his refrigerator at home. Cardiac workup was noncontributory, but a creatine kinase level greater than 6,000 warranted a muscle biopsy, which led to a diagnosis of McArdle disease. After four years of treatment without symptomatic improvement, a gradual transition of symptoms from pain alone to pain with stiffness, and in the wake of a positive GAD-antibody test, the diagnosis was changed to Stiff-Person Syndrome. This is the first known reported case that highlights the similarities between these two rare and distinct disease processes. Even though both McArdle disease and Stiff Person Syndrome are exceedingly rare, this case serves to highlight the importance of thorough history taking and keeping a broad differential with healthy skepticism of an existing diagnosis if the patient continues to have symptoms despite treatment.